Clinical evaluation of composite restorations placed on dimethyl sulfoxide-treated cervical carious lesions: a 36-month randomized double-blind controlled trial - Ismail, Omar Abdelaziz; Stape; Thiago Henrique Scarabello; Shaalan, Omar; Taymour, Noha; Basha, Ibrahim El-Dossoky; Alsamoully; Walaa Mohamed Ahmed; Tezvergil-Mutluay, Arzu (Elsevier, 2026)
Objectives: To evaluate the effect of a novel restorative approach using dimethyl sulfoxide (DMSO) as a cavity pretreatment on the material fracture and retention (primary outcome) of direct composite fillings placed on cervical carious lesions (CCLs).
Methods: 45 patients presenting CCLs were screened and randomized into two groups containing 37 caries lesions/group: an untreated control (20 patients) and a DMSO-treated (25 patients) group. Following a parallel-study design, two calibrated operators placed 74 (n = 37) composite fillings (Filtek Z350XT, 3 M ESPE) using a 2-step etch-and-rinse adhesive (Single Bond 2, 3 M ESPE). After baseline assessments (7 days), fillings were evaluated at 12-, 24- and 36-month follow-ups according to the FDI criteria (fracture/retention, marginal staining, marginal adaptation, postoperative sensitivity and caries recurrence). For statistical analysis, Chi-Square and Cochran's Q tests were used (α = 0.05) following the Bonferroni correction.
Results: DMSO had significant effects on the clinical performance of composite fillings placed on CCLs according to the FDI criteria (p < 0.05). Success rates after 36 months of untreated and DMSO-treated cavities were 65 % and 89 %, respectively, with a 70 % lower risk of failure when using DMSO. DMSO significantly reduced post-operative sensitivity and marginal staining and improved retention rates after 36 months (p < 0.05).
Conclusions: Long-term clinical performance of composite fillings using simplified etch-and-rinse adhesives can be optimized by employing DMSO as a cavity pretreatment.
Clinical significance: The use of DMSO can be a simple clinical approach to improve post-operative sensitivity of composite fillings, reduce risk of failures and extend service life by producing more stable composite-tooth interfaces.